2018
DOI: 10.1177/0018578718779009
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Meropenem After Reconstitution for Administration by Prolonged Infusion

Abstract: Objective: Meropenem is a parenteral carbapenem antibiotic which has a broad spectrum of activity against aerobes and anaerobes. Meropenem's bactericidal activity is determined by the time during which meropenem concentration remains above the minimal inhibition concentration (MIC) during the dosing interval. Thus, prolonged infusion is the optimal way to maximize the time-dependant activity. However, studies to date have shown that carbapenems and in particular, meropenem, are relatively unstable in solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Optimizing the duration of exposure may help in the adjustment of meropenem concentrations. Studies demonstrated that meropenem stability at room temperature is about 6–8 h. Therefore, it is necessary for a continuous infusion administration scheme to change the infusion bag periodically, avoiding loss of power and possible side effects due to exposure to harmful products that originated in meropenem degradation 41,45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimizing the duration of exposure may help in the adjustment of meropenem concentrations. Studies demonstrated that meropenem stability at room temperature is about 6–8 h. Therefore, it is necessary for a continuous infusion administration scheme to change the infusion bag periodically, avoiding loss of power and possible side effects due to exposure to harmful products that originated in meropenem degradation 41,45 …”
Section: Resultsmentioning
confidence: 99%
“…Studies demonstrated that meropenem stability at room temperature is about 6-8 h. Therefore, it is necessary for a continuous infusion administration scheme to change the infusion bag periodically, avoiding loss of power and possible side effects due to exposure to harmful products that originated in meropenem degradation. 41,45 Therapeutic drug monitoring is a practical way to assess exposure to antimicrobials in the right dosage, correlating with patients' clinical signs. TDM applies knowledge of PK/PD parameters and profiles, patients' physiology, and MIC of the causative pathogen to help guide therapy, individualize dose regimen and effectively eradicate infection.…”
Section: Re Sultsmentioning
confidence: 99%
“…The solution of IMP in normal saline solution was stable 3 to 4 h stored at 25 °C [ 22 ]. MER in 0.9% saline was stable at least 7 h if the temperature does not increase to 22 °C, while MER stability at 5 h when temperature does not exceed 33 °C [ 23 ]. Chlorhexidine combination with MER shown synergistic effects than IMP, and chlorhexidine together with IMP was indifferent in 10% of isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged infusions of antibiotics are already under study and have shown promising results. 13,14 There are, however, some key challenges to address for this scheme to be successfully implemented.…”
Section: Pragmatic Approaches For Cancer Care Continuummentioning
confidence: 99%